Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
[tex]x+3y=3\\3y=-x+3\\\\2x-3y=-12\\-3y=-2x-12\\3y=2x+12\\\\-x+3=2x+12=3y\\-9=3x\\-3=x\\\\(-3)+3y=3\\3y=6\\y=2[/tex]
x = -3
y = 2
x = -3
y = 2
get x on one side then you can use substitution
So, change x+3y=3 to x= -3y+3
Then plug in x to other equation to find y
2(-3y +3)-3y=-12
-6y + 6 -3y = -12
-9y = -18
Divide both sides by negative nine to find y
y = 2
Then plug in to original equation to find x
x + 3(2) = 3
x + 6 = 3
x = -3
So, y = 2 and x = -3
So, change x+3y=3 to x= -3y+3
Then plug in x to other equation to find y
2(-3y +3)-3y=-12
-6y + 6 -3y = -12
-9y = -18
Divide both sides by negative nine to find y
y = 2
Then plug in to original equation to find x
x + 3(2) = 3
x + 6 = 3
x = -3
So, y = 2 and x = -3
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.